Grambia: economic adjustment in a small open economy - Hadjimichael, Michael T.... el.al (I.M.F. WashingtonUS, 1992)
In 1985 Gambia implemented its Economic Recovery Program (ERP) aimed at restoring financial equilibrium and establishing sustainable economic growth. This was succeeded in 1990 by the Program of Sustained Development (PSD) which aimed at stimulating private sector development as well as continuing the thrust of ERP policies. This report focuses on Gambia's experiences in economic adjustment.